Implementation of Public Relations Ethics in Government Institutions - Soegiarto, Asep; Kholik, Abdul; Fatimah, Anggun Nadia; Putri, Salsabill Rizkina (Proceeding International Conference on Religion, Science and Education, 2024)
This article delves into the pivotal significance of ethical paradigms within the realm of public relations endeavors situated within governmental establishments. The cogent contemplation of ethical imperatives assumes a paramount role in upholding the tenets of lucidity, answerability, and the engendering of public confidence vis-à-vis the edicts and information promulgated by governmental entities. Employing a conceptual synthesis and a case study dissection, this manuscript elucidates the manner in which the integration of ethical precepts in public relations can enhance the caliber of governmental communication and fortify the interconnection between the administrative machinery and the population. Public relations ethics entails the steadfast adherence to ethical principles and professional benchmarks in the sphere of communication. The bedrock of ethical public relations practices is anchored in the principles of veracity, probity, and answerability. Within the context of governmental establishments, these principles assume an exacerbated significance, as they underpin the credibility of public policies and undertakings. Moreover, ethical commitment ensures that public relations agents operating within the governmental framework act consonant with the welfare of the public, thus fostering an environment of unreserved dialogue and an enlightened citizenry.